From individual to community : issues in development studies : essays in memory of Malcolm Adiseshiah - Saleth, R. Maria, 1955-; Adiseshiah, Malcolm S. (SAGE India, 2012)
From Individual to Community brings together a set of papers that provides critical commentaries on various facets of the ongoing process of development. The book addresses issues that concern developing countries--such as globalization, economic growth, rural transformation, gender equality, educational reforms and the Dalit movement--from a multidisciplinary perspective. Based on the theoretical framework of the normative principles, the book evaluates issues that are specifically relevant in the Indian context--rich versus poor, globalization versus sustainable development, and so on. Devoid o.